QUANTITATIVE ANALYSIS REGARDING PREGNANCY IN ADOLESCENCE IN A MUNICIPALITY IN MINAS GERAIS - Suelen Souza do Carmo; Darlan Einstein do Livramento; Hipólito Ferreira Paulino Neto; Mariana Gondim Mariutti Zeferino (Universidade Federal do Paraná, 2014)
This quantitative and descriptive study aimed to assess the frequency, causes, and consequences of pregnancy in adolescence. Interviews were held with 104 adolescents registered on the Live Births Information System in 2010, who were in the age range of 15 - 21 years old; the majority had low educational levels; 60% were not working; all attended prenatal care; changes were observed in their conjugal status after the pregnancy, as was increase in their knowledge and use of methods of contraception; 74% did not plan the pregnancy; and they reported changes following the pregnancy such as greater responsibility (26%) and loss of freedom (23%). It is concluded that it is necessary to become closer to the adolescents so as to clarify doubts, to break away from one's own prejudices, and to provide holistic care with objective, correct and clear guidance, respecting beliefs and individuality.